Inhibition of TLR4 Induces M2 Microglial Polarization and Provides Neuroprotection via the NLRP3 Inflammasome in Alzheimer’s Disease - Cui, Weigang; Sun, Chunli; Ma, Yuqi; Wang, Songtao; Wang, Xianwei; Zhang, Yinghua (Frontiers in Neuroscience, 2020)
Accumulating evidence has indicated that activation of microglia and neuroinflammation reaction play a prominent role in Alzheimer’s disease (AD). Inhibition of toll-like receptor 4 (TLR4) has been shown to be associated with immune responses and brain damage, but its effects on AD remain unclear. This study mainly aimed to investigate the protective effect of TAK-242 (TLR4-specific inhibitor) on microglial polarization and neuroprotection in an AD mouse model and the underlying mechanisms. We found that APP/PS1 transgenic AD mice exhibited a dramatic increase in TLR4 levels concomitant with a significantly higher expression of inflammatory microglia compared to C57BL/6 wild-type mice. Furthermore, inhibition of TLR4 by TAK-242 administration significantly improved neurological function, decreased the level of Bax, and caused a significant reduction in the levels of M1-markers (iNOS and TNFα), while the expressions of M2-phenotype markers (Trem-2 and Arg-1) were increased both in vivo and in vitro. Furthermore, TAK-242 treatment enhanced BV2 microglial phagocytosis. Moreover, Aβ25–35 caused the upregulation of inflammatory cytokine production, MyD88, NF-kappaB-p65, and NLRP3, which could be ameliorated by NLRP3-siRNA or TAK-242. These findings indicated that TLR4 inhibition provided neuroprotection and promoted a microglial switch from the inflammatory M1 phenotype to the protective M2 phenotype in AD. The mechanism involved may be related to modulation of the MyD88/NF-kappaB/NLRP3 signaling pathway.